Negative electrode binder, negative electrode plate and battery
By using the negative electrode adhesive containing aromatic organic acid, organic acid groups and acrylic structure units in the battery, and adjusting the contact angle of its negative album fluids, the existing battery negative adhesive is in mechanical machinery The lack of strength, flexibility and ion conduction capabilities significantly improve the battery's multiplier and circulation performance.
Patent Information
- Application Number
- CN202411944504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing battery negative electrode adhesives have shortcomings in improving battery magnification and circulation performance, especially in terms of mechanical strength, flexibility and ion conduction capabilities.
A negative adhesive, which includes a conjugate, a conjugate, a structural unit containing aromatic organic acids, the structure unit of the organic acid base group, and the acrylic structure unit, and the contact with the negative album fluid The angle is below 45 °.
This negative adhesive improves the peeling strength of the negative active substance layer and the negative episodes, enhances the battery's multiplication and circulation performance, and has good mechanical strength and flexibility.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to a negative electrode binder, a negative electrode sheet and a battery. Background Art
[0002] Battery negative electrode binder has a significant impact on improving the battery's rate performance, cycle life and safety, and plays a vital role in the battery.
[0003] At present, commonly used binders include polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), sodium alginate, styrene-butadiene rubber (SBR), etc. Among them, PVDF has good chemical stability, can resist the erosion of electrolyte, protect the negative electrode material from damage, and has high bonding strength, which can firmly bond the negative electrode materials together to form a stable electrode structure, but its insulation will lead to an increase in the internal resistance of the battery and affect the battery's charge and discharge efficiency. In addition, the ionic conductivity of PVDF is not high, which will affect the battery rate performance, and the fluorine element it contains will also have an impact on the environment. CMC has good bonding properties and can effectively bond the negative electrode materials together, but its mechanical strength is low and is not enough to support the stability of the negative electrode material. Sodium alginate is a natural polymer material with good biocompatibility and is environmentally friendly. It can form a stable bonding layer with the negative electrode material and improve the cycle stability of the electrode, but its conductivity is poor, which affects the battery rate and cycle performance. SBR is an elastomeric material with good flexibility and mechanical strength. It can enhance the mechanical stability of the negative electrode material and help resist volume changes during charging and discharging. However, its poor ion conductivity limits the rate performance of the battery.
[0004] Therefore, there is an urgent need for a new type of negative electrode binder that has high mechanical strength, flexibility and ion conductivity, so as to enhance the mechanical stability of the negative electrode material while improving the battery's rate, cycle and other performances. Summary of the invention
[0005] The present invention provides a negative electrode binder, a negative electrode sheet and a battery. The negative electrode binder has good ion transmission ability and can improve the peeling strength between the negative electrode active material layer and the negative electrode current collector, thereby improving the rate and cycle performance of the battery.
[0006] The present invention provides a negative electrode binder, comprising a copolymer, wherein the copolymer comprises a structural unit containing an aromatic organic acid salt, a structural unit containing an organic acid group and an acrylate structural unit; and the contact angle between the negative electrode binder and the negative electrode current collector is less than 45°.
[0007] Preferably, the glass transition temperature of the negative electrode binder is 35-60°C.
[0008] Preferably, in the copolymer, the mass ratio of the structural unit containing an aromatic organic acid salt, the structural unit containing an organic acid group, and the acrylic acid ester structural unit is 30-50:10-30:20-50.
[0009] Preferably, the structural unit containing an aromatic organic acid salt includes a styrene sulfonate structural unit; the structural unit containing an organic acid group includes an acrylic structural unit; the acrylic ester structural unit includes one or more of an ethyl (meth)acrylate structural unit, a propyl (meth)acrylate structural unit, a n-butyl (meth)acrylate structural unit, and an isooctyl (meth)acrylate structural unit.
[0010] Preferably, the copolymer further comprises an alcoholamine structural unit; in the copolymer, the mass ratio of the acrylate structural unit to the alcoholamine structural unit is 20-50:5-15.
[0011] Preferably, the alcoholamine structural unit includes an ethanolamine structural unit.
[0012] Another aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode binder described above.
[0013] According to one embodiment of the present invention, the negative electrode current collector is copper foil.
[0014] According to one embodiment of the present invention, the peel strength between the negative electrode active material layer and the negative electrode current collector is 8 N / m or more.
[0015] Another aspect of the present invention provides a battery, comprising a positive electrode sheet, a separator, and the negative electrode sheet.
[0016] The implementation of the present invention has at least the following beneficial effects: the negative electrode binder provided by the present invention contains a structural unit of an aromatic organic acid salt, a structural unit containing an organic acid group, and an acrylic acid ester structural unit, and the contact angle between the negative electrode binder and the negative electrode current collector is 45° or less. In particular, the contact angle between the copolymer and the negative electrode current collector is 45° or less, and at this time, the copolymer has suitable wettability and affinity with the negative electrode current collector and the negative electrode active material (especially graphite material), thereby effectively improving the bonding performance and the cycle performance of the battery. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] An embodiment of the present invention provides a negative electrode binder, including a copolymer, wherein the copolymer includes a structural unit containing an aromatic organic acid salt, a structural unit containing an organic acid group, and an acrylate structural unit; and the contact angle between the negative electrode binder and the negative electrode current collector is less than 45°.
[0019] According to the inventors' research, the organic acid groups in the aromatic organic acid salt structural units, under the action of aromatic conjugation, combined with the structural units containing organic acid groups, can better provide a stable transmission channel for active cations, promote the dissociation of ion pairs in the electrolyte, and enhance the migration of active cations. It can inhibit the shuttling of anions while attracting positively charged active cations. Under the action of the electric field, the active cations migrate between adjacent organic acid groups on the copolymer chain segments through the mechanism of "transition transmission".
[0020] At the same time, the presence of acrylic acid ester structural units gives the negative electrode binder a certain flexibility, while ensuring the swelling degree of the negative electrode binder in the electrolyte. The swollen negative electrode binder can form more ion transmission channels, thereby improving the ion transmission efficiency, thereby improving the battery's rate, cycle and other performance.
[0021] In addition, setting the contact angle between the negative electrode binder and the negative electrode current collector to 45° or less is very beneficial for further improving the bonding strength of the negative electrode binder and improving the cycle performance of the battery.
[0022] Further preferably, the contact angle between the negative electrode binder and the negative electrode current collector is 20°-40°, for example, 20°, 23°, 25°, 28°, 30°, 33°, 35°, 38°, 40° or a range consisting of any two thereof.
[0023] In the present invention, the contact angle between the negative electrode binder and the negative electrode current collector is the contact angle obtained by testing the water dispersion of the copolymer prepared by the negative electrode binder, the solid content of the water dispersion being 40%, under such conditions. The specific testing method is as follows: at room temperature, the negative electrode current collector is cut into square specimens of appropriate size, flatly adhered to a glass plate sample stand, the water dispersion is dropped on the surface of the negative electrode current collector, and the static contact angle is tested in air atmosphere using a JC2000D contact angle tester.
[0024] As is well known to those skilled in the art, the contact angle between the negative electrode binder and the negative electrode current collector can be adjusted by adjusting the specific substances and contents of the structural units containing aromatic organic acid salts, the structural units containing organic acid groups, and the acrylate structural units, as well as the conditions such as the selectively added auxiliary agents.
[0025] Preferably, the glass transition temperature of the negative electrode binder is 35-60°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or any two thereof. In this case, the negative electrode binder provided by the present invention has good flexibility, which is beneficial to improving the bonding strength of the binder and the cycle performance of the battery.
[0026] Preferably, in the copolymer, the mass ratio of the structural unit containing an aromatic organic acid salt, the structural unit containing an organic acid group, and the acrylic acid ester structural unit is 30-50:10-30:20-50.
[0027] In some embodiments, the mass ratio of structural units containing aromatic organic acid salts to structural units containing organic acid groups is 1:0.2~1, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or a range consisting of any two of them.
[0028] In some embodiments, the mass ratio of the structural units containing aromatic organic acid salts to the acrylic acid ester structural units is 1:0.4~1.7, for example, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7 or a range consisting of any two of them.
[0029] When the mass ratio of the structural unit containing an aromatic organic acid salt, the structural unit containing an organic acid group, and the acrylic ester structural unit is within the above range, it is beneficial to the transmission of active cations, improves the binding force between the negative electrode active material layer and the negative electrode current collector, reduces the glass transition temperature of the negative electrode binder, gives the negative electrode binder a certain flexibility, and improves the battery rate and cycle performance.
[0030] Preferably, the structural unit containing an aromatic organic acid salt includes a p-styrene sulfonate structural unit, more preferably a p-styrene sulfonate lithium structural unit. The p-styrene sulfonate lithium structural unit can increase the concentration of lithium ions in the electrolyte and improve the migration rate of lithium ions to a certain extent.
[0031] Preferably, the structural unit containing an organic acid group includes an acrylic structural unit. In the present invention, the carboxylic acid group in the structural unit containing a carboxylic acid group can improve the binding force between the negative electrode active material layer and the negative electrode current collector, thereby improving the cycle life of the battery.
[0032] Preferably, the acrylic acid ester structural unit includes a (meth) acrylic acid ester structural unit, and the (meth) acrylic acid ester structural unit includes one or more of an ethyl (meth) acrylate structural unit, a propyl (meth) acrylate structural unit, a n-butyl (meth) acrylate structural unit, and an isooctyl (meth) acrylate structural unit.
[0033] In the present invention, (meth)acrylate refers to acrylate or methacrylate. For example, the (meth)acrylate structural unit refers to acrylate structural unit or methacrylate structural unit.
[0034] Preferably, the copolymer further comprises an alcohol amine structural unit. When the alcohol amine structural unit is present in the copolymer, the affinity between the negative electrode binder and the negative electrode active material and the negative electrode current collector can be improved, which is beneficial to further improve the bonding strength of the negative electrode binder and the cycle performance of the battery.
[0035] In the copolymer, the mass ratio of the acrylic acid ester structural unit to the alcohol amine structural unit is 20-50:5-15.
[0036] In a specific implementation, the mass ratio of the acrylate structural unit to the alcoholamine structural unit is 1:0.1-0.75, for example, 1:0.12, 1:0.15, 1:0.17, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.75 or a range consisting of any two of them.
[0037] Preferably, the alcoholamine structural unit includes an ethanolamine structural unit, as shown in Formula 1:
[0038] Formula 1.
[0039] In the present invention, as is well known to those skilled in the art of chemical synthesis, the above-mentioned "certain" structural unit represents a structural unit in which the corresponding structure of the monomer in the polymer obtained by polymerization of a "certain" monomer exists in the polymer. For example, the acrylate structural unit represents a corresponding structural unit existing in the copolymer after the acrylate monomer is polymerized.
[0040] Similarly, in the above-mentioned copolymer, the mass ratio between the various structural units is based on the mass ratio of the various monomers participating in the polymerization reaction, and the preparation process basically does not affect the mass ratio between the various structural units. That is, when the above-mentioned copolymer is formed by copolymerizing monomers containing aromatic organic acid salts, monomers containing organic acid groups, acrylate monomers and other raw materials, the mass ratio between the aromatic organic acid salt monomers, monomers containing organic acid groups, acrylate monomers and other raw materials is basically equal to the mass ratio between the structural units containing aromatic organic acid salts, structural units containing organic acid groups and acrylate structural units in the prepared copolymer.
[0041] The embodiment of the present invention also provides a method for preparing the above-mentioned negative electrode binder, comprising the following steps: polymerizing a raw material system including a monomer of an aromatic organic acid salt, a monomer containing an organic acid group, and an acrylate monomer to obtain a polymer product as the copolymer of the present invention. Preferably, the above-mentioned polymer product can be polymerized with an alcoholamine compound to obtain a copolymer, and the alcoholamine compound includes ethanolamine.
[0042] In the specific implementation, a solvent and a surfactant are added to a reaction kettle, and then the solvent, the surfactant, the monomer containing an aromatic organic acid salt, the monomer containing an organic acid group, and the acrylate monomer are mixed and pre-emulsified at a high speed to obtain a uniform pre-emulsified liquid, which is transferred to a constant pressure dropping funnel for use.
[0043] In the specific implementation, high-purity nitrogen is introduced into the reactor to replace the air, the heating and stirring of the reactor are turned on to raise the temperature to 60-70°C, and the stirring and nitrogen are continuously introduced until the reaction is completed. When the reaction temperature is reached, an initiator is added, and the constant pressure dropping funnel is opened to drop the pre-emulsion to carry out a polymerization reaction. After the addition of the pre-emulsion is completed, the temperature is continued to be raised to 70-85°C, the initiator is added again, and the stirring is continued for heat preservation and aging, and then the temperature is continued to be raised to 80-85°C, and the alcoholamine compound is added to continue the reaction. After the reaction is completed, the temperature is lowered, and it is cooled to ≤40°C and filtered to obtain the negative electrode binder.
[0044] In some embodiments, the raw material system further includes an initiator, a surfactant, and a solvent.
[0045] In a specific implementation, the mass ratio of the initiator, the surfactant, the solvent and the acrylate monomer is 0.5-3:0.3-1:100-300:20-50.
[0046] In a specific implementation, the mass ratio of the initiator to the acrylate monomer is 1:7-100, for example, 1:7, 1:10, 1:20, 1:25, 1:30, 1:35, 1:40, 1:40, 1:50, 1:60, 1:65, 1:70, 1:75, 1:80, 1:90, 1:100 or a range consisting of any two of them.
[0047] In addition, the mass ratio of the surfactant to the acrylate monomer can be 1:20~167, for example, 1:20, 1:35, 1:50, 1:65, 1:70, 1:75, 1:90, 1:95, 1:100, 1:105, 1:110, 1:130, 1:150, 1:165, 1:167 or a range consisting of any two of them.
[0048] In addition, the mass ratio of the solvent to the acrylate monomer can be 1:0.07~0.5, for example, 1:0.07, 1:0.08, 1:0.1, 1:0.13, 1:0.15, 1:0.18, 1:0.2, 1:0.23, 1:0.25, 1:0.28, 1:0.3, 1:0.4, 1:0.5 or a range consisting of any two of them.
[0049] Specifically, the initiator includes a peroxide initiator, and the peroxide initiator includes one or more of ammonium persulfate, potassium persulfate and sodium persulfate, which is beneficial to the polymerization reaction.
[0050] Specifically, the surfactant includes one or more of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.
[0051] In specific implementation, the anionic surfactant includes one or more of sodium dodecyl sulfate, sodium octadecyl sulfate, and sodium dodecylbenzene sulfonate. For example, the cationic surfactant includes hexadecyltrimethyl quaternary ammonium bromide, the amphoteric surfactant includes dodecylaminopropionic acid, and the nonionic surfactant includes polyoxyethylene ether.
[0052] Specifically, the solvent includes water.
[0053] The embodiment of the present invention also provides a negative electrode sheet, a negative electrode current collector, and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer includes the above-mentioned negative electrode binder or the negative electrode binder prepared according to the above-mentioned preparation method of the negative electrode binder.
[0054] In a specific implementation, the negative electrode active material layer also includes a negative electrode active material, a negative electrode conductive agent, and a thickener. The negative electrode active material may include one or more of hard carbon and lithium titanate; the negative electrode conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fiber; the thickener may include sodium carboxymethyl cellulose, and the negative electrode current collector may include copper foil.
[0055] In the embodiment of the present invention, the negative electrode sheet can be prepared by conventional methods in the art, for example, by a coating method. Specifically, the components used to form the negative electrode active material layer, such as the negative electrode active material, the conductive agent, the thickener, and the negative electrode binder, can be dispersed in a negative electrode solvent, such as water, to prepare a negative electrode slurry, which is then coated on the surface of the negative electrode current collector, and after drying, rolling, and other processes, the negative electrode sheet is prepared. Among them, the coating, drying, rolling, and other processes involved are conventional operations for preparing negative electrode sheets by coating methods, and are not particularly limited thereto.
[0056] In some embodiments, the peel strength between the negative electrode active material layer and the negative electrode current collector is greater than 8 N / m, preferably greater than 10 N / m.
[0057] An embodiment of the present invention further provides a battery, comprising a positive electrode sheet, a separator, and the negative electrode sheet mentioned above.
[0058] In some embodiments, the battery may be a lithium-ion battery, which has advantages corresponding to those of the negative electrode binder, and will not be described in detail.
[0059] Generally, a battery includes a cell, an electrolyte, and a shell that encapsulates the cell. The electrolyte is injected into the cell in the shell. The cell includes a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet. The cell can be a laminated cell, that is, the cell is formed by alternating positive electrode sheets, separators, and negative electrode sheets.
[0060] The embodiments of the present invention can prepare batteries by conventional methods in the art. For example, the positive electrode sheets, separators, and negative electrode sheets can be alternately stacked to prepare a laminated battery cell. The battery cell is then placed in a shell and subjected to conventional processes such as liquid injection (i.e., injecting electrolyte), packaging, standing, formation, and capacity division to prepare a battery.
[0061] Specifically, the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer located on at least one side surface of the positive electrode collector. Specifically, the positive electrode active material layer can be arranged on one side surface of the positive electrode collector, or the positive electrode active material layer can be arranged on the surfaces of the opposite sides in the thickness direction of the positive electrode collector.
[0062] Specifically, the positive electrode active material layer may include a positive electrode active material, a conductive agent and a positive electrode binder, all of which may be conventional materials in the art. For example, the positive electrode active material may include one or more of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and a positive electrode ternary material. The positive electrode ternary material may include a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material. The conductive agent may include one or more of conductive carbon black (Super. P), conductive graphite, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber. The positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, and the like.
[0063] The embodiment of the present invention may adopt a conventional positive electrode current collector in the art, for example, the positive electrode current collector includes aluminum foil.
[0064] In the embodiment of the present invention, the positive electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the components used to form the positive electrode active material layer, such as the positive electrode active material, the conductive agent, and the positive electrode binder, can be dispersed in a positive electrode solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry, which is then coated on the surface of the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is prepared. Among them, the coating, drying, rolling and other processes involved are conventional operations for preparing positive electrode sheets by coating, and there is no special limitation on this.
[0065] In the embodiment of the present invention, the separator is used to separate the positive electrode sheet and the negative electrode sheet to avoid short circuit between the positive electrode sheet and the negative electrode sheet. The embodiment of the present invention can adopt conventional separators in the art, for example, the separator includes polypropylene film (PP film) and polyethylene (PE), but is not limited thereto.
[0066] In the embodiment of the present invention, the electrolyte may be a non-aqueous electrolyte, which generally includes a lithium salt, a carbonate solvent and an additive, wherein the carbonate solvent may include one or more of a cyclic carbonate solvent and a chain carbonate solvent, specifically including one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6) and lithium perchlorate, and the additive may include one or more of fluoroethylene carbonate, difluoroethylene carbonate, fluorocyclotriphosphazene, and hexafluorocyclotriphosphazene.
[0067] In the embodiment of the present invention, the battery cell may be packaged with conventional shell materials in the art, and the shell may include, for example, soft packaging materials such as aluminum-plastic film (the battery in this case is a soft-package battery), but is not limited thereto.
[0068] The present invention is further described below through specific embodiments.
[0069] Example 1
[0070] 1. Preparation of pre-emulsion
[0071] (1) In parts by mass, 40 parts of deionized water and 0.1 parts of a surfactant (sodium dodecylbenzene sulfonate) were added to a reaction kettle. After 150 parts of deionized water, 0.2 parts of a surfactant (sodium dodecylbenzene sulfonate), 30 parts of lithium p-styrene sulfonate, 20 parts of acrylic acid, and 30 parts of ethyl acrylate monomer were mixed, high-speed pre-emulsification was performed to obtain a uniform pre-emulsion, and the pre-emulsion was transferred to a constant pressure dropping funnel for standby use.
[0072] 2. Preparation of polymer products
[0073] High-purity nitrogen was introduced into the reactor to replace the air; the heating and stirring of the reactor were turned on to increase the temperature; stirring and nitrogen were kept until the end of the reaction, and when the reaction temperature reached 65°C, 0.5 parts of initiator (sodium persulfate) were added, and the constant pressure dropping funnel was opened to start dropping the pre-emulsion to react. After the addition of the pre-emulsion was completed, the temperature was continued to rise to 70°C, 0.2 parts of initiator (sodium persulfate) were added, and stirring was continued to keep warm and mature for 3 hours.
[0074] 3. Introduction of amine structural units: Continue to heat up to 75°C, then use a constant pressure funnel to drop 5 parts of ethanolamine, continue to react for 2 hours, and start to cool after the reaction is completed. Cool and filter to obtain the negative electrode binder.
[0075] 4. Preparation of batteries
[0076] (1) Preparation of positive electrode
[0077] Preparation of positive electrode sheet: By mass, 96.80 parts of nickel cobalt lithium manganese oxide ternary material, 1.5 parts of conductive agent Super.P, 0.5 parts of conductive graphite KS-6, 1.20 parts of positive electrode binder polyvinylidene fluoride and N-methylpyrrolidone were mixed to prepare positive electrode slurry, and then the positive electrode slurry was coated on the front and back surfaces of aluminum foil, and the positive electrode sheet was obtained after drying and rolling.
[0078] (2) Preparation of negative electrode
[0079] Artificial graphite, conductive carbon black, sodium carboxymethyl cellulose, and the negative electrode binder obtained in step 3 are mixed in a mass ratio of 93:3:2:2, and deionized water is added and stirred evenly to prepare a negative electrode slurry;
[0080] The negative electrode slurry is coated on the front and back surfaces of the copper foil, and after drying and rolling, a negative electrode coating is formed on the front and back surfaces of the copper foil to obtain a negative electrode sheet.
[0081] (3) Battery assembly
[0082] The positive electrode sheet, the separator (PE film) and the negative electrode sheet are alternately stacked to form a stacked battery cell;
[0083] The laminated battery cell is placed in an aluminum-plastic film, and the injection port is retained, and the electrolyte is injected into it through the injection port, and then the injection port is closed to obtain a battery precursor; after aging, formation and aging treatment, and after processes such as capacity separation, a soft-pack battery is obtained. Among them, the electrolyte is composed of EC, DEC, EMC and LiPF6, the mass ratio of EC, DEC and EMC is 1:2:1, and the concentration of LiPF6 in the electrolyte is 1 mol / L.
[0084] Example 2
[0085] A negative electrode binder and a battery were prepared according to the method of Example 1, except that the added amounts of monomers containing aromatic organic acid salts, monomers containing organic acid groups, acrylate monomers, and alcoholamine monomers were as follows: 40 parts of lithium p-styrene sulfonate, 20 parts of acrylic acid, 30 parts of ethyl acrylate, and 10 parts of ethanolamine.
[0086] Example 3
[0087] A negative electrode binder and a battery were prepared according to the method of Example 1, except that the added amounts of monomers containing aromatic organic acid salts, monomers containing organic acid groups, acrylate monomers, and alcoholamine monomers were as follows: 50 parts of lithium p-styrene sulfonate, 10 parts of acrylic acid, 20 parts of ethyl acrylate, and 15 parts of ethanolamine.
[0088] Example 4
[0089] A negative electrode binder and a battery were prepared according to the method of Example 1, except that the added amounts of monomers containing aromatic organic acid salts, monomers containing organic acid groups, acrylate monomers, and alcoholamine monomers were as follows: 30 parts of lithium p-styrene sulfonate, 30 parts of methacrylic acid, 50 parts of methacrylate, and 6 parts of ethanolamine.
[0090] Comparative Example 1
[0091] A negative electrode binder and a battery were prepared according to the method of Example 1, except that ethanolamine was not included.
[0092] Comparative Example 2
[0093] A negative electrode binder and a battery were prepared according to the method of Example 2, except that lithium p-styrene sulfonate was not included.
[0094] Comparative Example 3
[0095] A negative electrode binder and a battery were prepared according to the method of Example 2, except that acrylic acid was not included.
[0096] Comparative Example 4
[0097] A battery was prepared according to the method of Example 1, except that PVDF was used as the negative electrode binder.
[0098] Comparative Example 5
[0099] A battery was prepared according to the method of Example 1, except that SBR was used as the negative electrode binder.
[0100] The performance tests of the negative electrode binder, negative electrode sheet and battery in the embodiment and the comparative example were carried out through the following processes respectively. The results are shown in Table 1:
[0101] (1) Contact angle test
[0102] The negative electrode current collector (copper foil) was cut into square samples of appropriate size and flatly adhered to a glass plate sample stand. The negative electrode binder prepared in the embodiment was adjusted to a solid content of 40%, and dropped on the surface of the negative electrode current collector. The static contact angle was tested in air atmosphere using a JC2000D contact angle tester.
[0103] (2) Glass transition temperature test
[0104] The glass transition temperature Tg of the negative electrode binder of the embodiment and the comparative example was detected using a differential scanning calorimeter (Shanghai Qunhong Instrument Equipment Co., Ltd., model: DSC-100). The steps include: turning on high-purity nitrogen, setting the nitrogen flow rate to 0.5-0.6 L / min, turning on the DSC power supply, and running the desktop. Set the temperature: -60 ℃, constant temperature for 10 min, -60 ℃~80 ℃, heating rate 10 K / min, after setting, put the prepared sample (negative electrode binder) into the heating furnace, cover the furnace body protection cover, and add an appropriate amount of liquid nitrogen to the constant temperature tank. When the sample temperature reaches -60 ℃, run the test.
[0105] (3) Negative electrode peel strength test
[0106] The peel strength (adhesion) of the negative electrode sheet was measured using a tensile testing machine. The test method was based on GB2792-2014.
[0107] (4) Cycle test
[0108] At 25°C, the battery was charged to 4.50 V at a constant current of 1 C, then charged to 4.50 V at a constant voltage of 0.05 C, and then discharged to 3.0 V at a discharge rate of 1 C. This charge and discharge cycle was repeated 200 times, and the discharge capacity at the first cycle (Q1) and the discharge capacity at the 200th cycle (Q 200 ). The capacity retention rate Q after 200 cycles is calculated according to the following formula: Capacity retention rate Q = Q200 / Q1 100%.
[0109] (5) Rate test (testing the rate performance of the prepared battery cell at room temperature)
[0110] First, charge to 4.2 V at a constant current of 0.5 C, then charge at a constant voltage of 4.2 V, and end charging when the current drops to 0.05 C; secondly, discharge to 3.0 V at a constant current of 0.2 C, end discharge, stand for 10 min, and record discharge capacity; then charge to 4.2 V at a constant current of 0.5 C, then charge at a constant voltage of 4.2 V, and end charging when the current drops to 0.05 C; finally, discharge the battery at rates of 0.5 C, 1 C, 2 C, 3 C, and 5 C according to the above steps, and the ratio of the discharge specific capacity at 3 C to the discharge specific capacity at 0.5 C is used as the basis for judging the rate performance.
[0111] Table 1
[0112]
[0113] It can be seen from the test results in Table 1 that, compared with Comparative Examples 1 to 5, the negative electrode binders in Examples 1 to 4 contain structural units of aromatic organic acid salts, structural units containing organic acid groups, and acrylic acid ester structural units, and the contact angle between the negative electrode binder and the negative electrode current collector is less than 45°, and the negative electrode binder has good ion transport capability, and can improve the peel strength between the negative electrode active material layer and the negative electrode current collector, thereby improving the rate and cycle performance of the battery.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode binder, characterized in that: The copolymer comprises a structural unit containing an aromatic organic acid salt, a structural unit containing an organic acid group, and an acrylic acid ester structural unit; The contact angle between the negative electrode binder and the negative electrode current collector is 45° or less.
2. The negative electrode binder according to claim 1, characterized in that The glass transition temperature of the negative electrode binder is 35-60°C.
3. The negative electrode binder according to claim 1, characterized in that In the copolymer, the mass ratio of the structural unit containing an aromatic organic acid salt, the structural unit containing an organic acid group, and the acrylic acid ester structural unit is 30-50:10-30:20-50.
4. The negative electrode binder according to any one of claims 1 to 3, characterized in that: The structural unit containing an aromatic organic acid salt includes a styrene sulfonate structural unit; the structural unit containing an organic acid group includes an acrylic structural unit; the acrylic ester structural unit includes one or more of an ethyl (meth)acrylate structural unit, a propyl (meth)acrylate structural unit, a n-butyl (meth)acrylate structural unit, and an isooctyl (meth)acrylate structural unit.
5. The negative electrode binder according to claim 1, characterized in that The copolymer further comprises an alcoholamine structural unit; in the copolymer, the mass ratio of the acrylic ester structural unit to the alcoholamine structural unit is 20-50:5-15.
6. The negative electrode binder according to claim 5, characterized in that The alcoholamine structural unit includes an ethanolamine structural unit.
7. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode binder according to any one of claims 1 to 6.
8. The negative electrode sheet according to claim 7, characterized in that: The negative electrode current collector is copper foil.
9. The negative electrode sheet according to claim 8, characterized in that: The peel strength between the negative electrode active material layer and the negative electrode current collector is greater than 8 N / m.
10. A battery, characterized in that: It comprises a positive electrode sheet, a separator, and the negative electrode sheet according to any one of claims 7 to 9.
Citation Information
Patent Citations
Lithium-sulfur battery binder and preparation method and application thereof
CN111092226A
Anode water-based adhesive capable of improving discharge platform of lithium ion battery and preparation method of anode water-based adhesive
CN116936807A
Carbon-coated aluminum foil water-based adhesive as well as preparation method and application thereof
CN118978879A
Binder for lithium ion secondary battery negative electrode, and lithium ion secondary battery with binder for negative electrode
JP2013033692A
Binder with good rate property and long cycleability for lithium secondary battery
US20060257739A1